2012
DOI: 10.1111/j.1365-2311.2012.01380.x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐specific foraging by leafcutter ant workers (Atta cephalotes, Hymenoptera: Formicidae)

Abstract: 1. Sodium is often a limiting nutrient for terrestrial animals, and may be especially sought by herbivores. Leafcutter ants are dominant herbivores in the Neotropics, and leafcutter foraging may be affected by nutritional demands of the colony and/or the demands of their symbiotic fungal mutualists. We hypothesized that leafcutter colonies are sodium limited, and that leafcutter ants will therefore forage specifically for sodium.2. Previous studies demonstrated that leafcutter Atta cephalotes Linnaeus workers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Recent work has emphasized the potential importance of less-studied elements that exist in both organic molecules and ionic forms, but are essential to herbivores (Behmer and Joern, 2012; Joern et al, 2012). Sodium can be limiting for insect herbivores because it occurs in low concentration in plant tissues (Kaspari et al, 2008; Behmer and Joern, 2012; Chavarria Pizarro et al, 2012), and potassium was also identified as a predictor of insect herbivore abundance (Joern et al, 2012). If AMF alter plant concentrations of these elements (in organic or inorganic forms) that are important to insect nutrition, it may provide an additional mechanism of indirect mycorrhizal effects on insect herbivore preference and performance.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has emphasized the potential importance of less-studied elements that exist in both organic molecules and ionic forms, but are essential to herbivores (Behmer and Joern, 2012; Joern et al, 2012). Sodium can be limiting for insect herbivores because it occurs in low concentration in plant tissues (Kaspari et al, 2008; Behmer and Joern, 2012; Chavarria Pizarro et al, 2012), and potassium was also identified as a predictor of insect herbivore abundance (Joern et al, 2012). If AMF alter plant concentrations of these elements (in organic or inorganic forms) that are important to insect nutrition, it may provide an additional mechanism of indirect mycorrhizal effects on insect herbivore preference and performance.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, AMF derived from both organic and conventional farms resulted in plants with nearly double the Na content of commercial AMF plants. Sodium has recently received greater attention as an important nutrient for herbivores given its generally low concentration in plant relative to herbivore tissues (Kaspari et al 2008, Chavarria Pizarro et al 2012. Thus, farm AMF communities may have mixed effects on foliage nutrient quality for herbivores by decreasing availability of one potentially limiting element (P) but increasing another (Na).…”
Section: Leaf and Root Traitsmentioning
confidence: 99%
“…Since plant tissues are deficient in key micronutrients, foraging on nonplant resources is thought to function as dietary supplementation (Dudley et al ., 2012). In particular, this behaviour is common among herbivorous social insects that maintain multiple life stages—each of which has different nutritional requirements—within a colony (Kaspari et al ., 2009; Chavarria Pizarro et al ., 2012). Yet, apart from sodium, the foraging behaviour and preferences of social insects for micronutrients is largely unknown.…”
Section: Introductionmentioning
confidence: 99%